Pengaruh Lingkungan Kerja Dan Budaya Organisasi Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Pdam Tirta Sanjung Buana Sijunjung - Tasya Auliana; Marta Widian Sari; Yosi Puspita Sari (CV. ITTC INDONESIA, 2026)
This study aims to determine and analyze the influence of the work environment and organizational culture on employee performance, both directly and indirectly through job satisfaction as an intervening variable at PDAM Tirta Sanjung Buana Sijunjung. This research employs a quantitative method with a causal associative approach. The population in this study comprises all employees of PDAM Tirta Sanjung Buana Sijunjung, totaling 52 people. Due to the small population size, the sampling technique used was saturated sampling (census), where the entire population served as respondents. Data analysis was conducted using Structural Equation Modelling (SEM) based on Partial Least Square (PLS) with the assistance of SmartPLS 3.0 software.The results of this study indicate that: (1) Work environment has a positive and significant effect on job satisfaction; (2) Organizational culture has a positive and significant effect on job satisfaction; (3) Directly, the work environment has a negative and insignificant effect on employee performance; (4) Directly, organizational culture has a negative and insignificant effect on employee performance; (5) Job satisfaction has a positive and significant effect on employee performance; (6) Work environment has a positive and significant effect on employee performance through job satisfaction as an intervening variable; and (7) Organizational culture has a positive and significant effect on employee performance through job satisfaction as an intervening variable. These findings demonstrate that improvements in the work environment and organizational culture do not directly improve performance but are effective when mediated by employee job satisfaction.